Exploring pathways for sustained melanogenesis in facial melasma: an immunofluorescence study - Espósito, A. C.C. [UNESP]; Brianezi, G. [UNESP]; de Souza, N. P. [UNESP]; Miot, L. D.B. [UNESP]; Marques, M. E.A. [UNESP]; Miot, H. A. [UNESP] (Wiley, 2018)
Background: The physiopathology of epidermal hypermelanization in melasma is not completely understood. Several cytokines and growth factors are increased in skin with melasma, nevertheless, nor the pathways involved in the increased αMSH expression have been adequately evaluated, nor a model for sustained focal melanogenesis is available. Objective: To explore stimulatory pathways for epidermal pigmentation in facial melasma related to αMSH: those linked to ultraviolet radiation, oxidative stress, inflammation, neural crest pigmentation cell differentiation and antagonism of αMSH. Methods: Paired skin biopsies (3 mm) from 26 women with facial melasma and from normal adjacent skin (<2 cm far) were processed for immunofluorescence with markers for p53, p38, αMSH, MC1R, Melan-A, IL-1α, COX2, Wnt1, WIF-1 and ASIP. Results: The fluorescence intensity in the skin from melasma was higher for MC1R, αMSH at epidermis as at melanocytes (P < 0.05). There were no differences between the sites in epidermal protein expression of COX2, IL-1α, p53, WIF-1 and ASIP (P > 0.1). P53 was expressed only in epidermis, without difference between sites (P = 0.92). WNT1 was remarkable in the epidermis of melasma (P < 0.01), but not in dermis. Positive p38 cells were prominent in the upper dermis of melasma (P < 0.01), despite no marking in epidermis. Conclusion: Melanogenesis in melasma involves epithelial secretion of αMSH and activation of the Wnt pathway; nevertheless, it seems to be independent of the stimulation by ultraviolet radiation/p53, IL-1α, COX2/PgE2, WIF-1 and ASIP. Damaged cells at upper dermis suggest the role of senescence/autophagy in sustained pigmentation in melasma.
Keywords: COX2; melanin; melasma; p38; p53; pigmentation; ultraviolet radiation; α MSH